دور الاتصال الطبي في رفع مستوى التوعية الصحية دراسة ميدانية على صيدليات بلدية المقرن ولاية الوادي - ميلود قصبة; رابح بن ققة (جامعة الوادي - University of Eloued, 2025)
"هدفت الدراسة إلى الكشف عن دور الاتصال الطبي في تعزير مستوى التوعية الصحية لدى الأفراد، من خلال دراسة ميدانية أجريت على صيدليات بلدية المقرن بولاية الوادي. ارتكز البحث على المنهج الوصفي التحليلي، لما له من قدرة على وصف الظاهرة وتحليل علاقاتها، وتم العمل بمقابلة مع 7 من الصيادلة طرحت عليهم أسئلة حول موضوع وكذلك تم توزيع استبيان على عينة عشوائية بسيطة مكونة من 140 مفردة من مرتادي الصيدليات، واحتوى على 49 بندا موزعة على أربعة محاور رئيسية. تناولت الدراسة العلاقة بين الاتصال الطبي كمتغير مستقل والتوعية الصحية كمتغير تابع، وسعت إلى قياس أثر الأساليب التفاعلية، وجودة المعلومات المقدمة من الصيادلة، والتحديات التي تواجه عملية التواصل، على مدى إدراك المرضى وفهمهم للمعلومات الصحية والتزامهم بالتعليمات العلاجية. توصلت الدراسة الى أن الاتصال الطبي الجيد لع دور فعال في رفع وعي الأفراد وتحسين سلوكهم الصحي. وقد خلصت الدراسة إلى أهمية تكوين الصيادلة في مهارات الاتصال وتفعيل الوسائط الرقمية لنشر الرسائل الصحية، وأوصت بتطوير المحتوى الصحي المقدم للمرضى بشكل يسهم في الوقاية والتثقيف. "The study aimed to uncover the role of medical communication in enhancing health awareness among individuals, through a field study conducted in the pharmacies of the Municipality of Magrane in El Oued Province. The research was based on the descriptive-analytical method due to its ability to describe the phenomenon and analyze its relationships. Interviews were conducted with 7 pharmacists who were asked questions related to the topic, and a questionnaire was distributed to a simple random sample of 140 pharmacy visitors. The questionnaire included 49 items distributed across four main axes. The study examined the relationship between medical communication as an independent variable and health awareness as a dependent variable. It aimed to measure the impact of interactive methods, the quality of information provided by pharmacists, and the challenges facing the communication process on patients’ understanding and perception of health information as well as their adherence to treatment instructions. The study found that effective medical communication plays a vital role in raising individuals’ awareness and improving their health behavior. It concluded with the importance of training pharmacists in communication skills and activating digital media to disseminate health messages. The study recommended developing the health content provided to patients in a way that contributes to prevention and education."
مذكرة ماستر قسم علوم الاجتماعية تخصص علم اجتماع الاتصال
Keywords: التواصل الطبي; التوعية الصحية; الصيادلة; المعلومات الصحية; تثقيف المرضى; Medical communication; health awareness; pharmacists; health information; patient education